USM IO REBRANDED 10 AS USM-IMCC - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 9 February 2017 – The Universiti Sains Malaysia (USM) International Office (IO) has undergone a rebranding exercise and is now known as the USM International Mobility and Career Centre (USMIMCC).